The Role of Vitamin D in TNF-α Levels in Pulmonary TB Patients - Sahidan, Sahidan; Sulistyasmi, Wiwit; Farizal, Jon; Hartini, Supri; Ujiani, Sri (Borneo Scientific Publishing, 2026)
Tuberculosis (TB) remains a major global health problem, with immune responses particularly tumor necrosis factor-alpha (TNF-α) playing a key role in disease progression. Vitamin D, synthesized through sunlight exposure, has been suggested to modulate immune responses; however, its effect on TNF-α in TB patients remains unclear. This study aimed to evaluate the effect of sunlight exposure on TNF-α levels in patients with pulmonary tuberculosis. A quasi-experimental pre–post study was conducted among 60 TB patients divided into control and intervention groups. TNF-α levels were measured before and after intervention and analyzed using appropriate statistical tests, including the Wilcoxon signed-rank test. The results showed a slight increase in mean TNF-α levels after sunlight exposure; however, the difference was not statistically significant (p = 0.475). Increased variability in TNF-α levels after the intervention suggests heterogeneous individual responses. These findings indicate that sunlight exposure may have a limited effect on TNF-α modulation in TB patients. Further studies with larger sample sizes and comprehensive biomarker assessments are needed to clarify the relationship between sunlight exposure, vitamin D, and immune responses in tuberculosis.